Activated carbons derived from tamarind seeds for hydrogen storage. (December 2015) - Ramesh, T.; Rajalakshmi, N.; Dhathathreyan, K.S.
Graphical abstract: Hydrogen storage by activated carbons from tamarind seeds were studied. The carbonisation method, concentration of activating agent (KOH), duration etc., play a major role in increasing the surface area and micrpores in the activated carbons, which increases the hydrogen storage capacity from 0.54 to 4.6 wt% at RT and at 4 Mpa. Abstract: To make hydrogen economy a reality, the key technical challenges that need to be addressed are Hydrogen generation, transmission and storage for application in fuel cells. Among them, H2 storage presents a major challenge to material scientists to meet the USDOE target of 5.5 wt%. The present paper investigates the hydrogen storage capacity of activated carbons derived from tamarind seeds by thermal, microwave and by chemical KOH activation treatment. The various parameters optimised to obtain high hydrogen storage capacity are KOH concentration, duty cycle of microwave pulsing, carbonization, hydrogen adsorption conditions etc., The surface area, micropore volume, pore size and nitrogen adsorption measurements were determined for all the samples and found that the carbonization temperature and concentration of KOH play a major role in increasing the surface area, micropore volume and pore size. We have obtained a high surface area activated carbon of 1785 m 2  g −1, micropore volume of 0.94 cm 3  g −1 and pore size of around 0.8–1.1 nm. The maximum hydrogen storage capacity of these activated carbons from tamarind seeds at RT and 4.0 MPa was found to be 4.73 wt%, which is about 80% of the USDOE target. The samples also show good cyclic stability for hydrogen adsorption and desorption studies. These results suggest that activated carbons fabricated from tamarind seeds with high surface area and micropore volume will be an ideal candidate for hydrogen storage.